VO2 requirements of boxing exercises - Arseneau, E.; Mekary, S.; Léger, L. A. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to quantify the physiological requirements of various boxing exercises such as sparring, pad work, and punching bag. Because it was not possible to measure the oxygen uptake (Vo2) of "true" sparring with a collecting gas valve in the face, we developed and validated a method to measure Vo2 of "true" sparring based on "postexercise" measurements. Nine experienced male amateur boxers (Mean ± SD: age = 22.0 ± 3.5 years, height = 176.0 ± 8.0 cm, weight = 71.4 ± 10.9 kg, number of fights = 13.0 ± 9.5) of regional and provincial level volunteered to participate in 3 testing sessions: (a) maximal treadmill test in the LAB, (b) standardized boxing training in the GYM, and (c) standardized boxing exercises in the LAB. Measures of Vo2, heart rate (HR), blood lactate concentration [LA], rated perceived exertion level, and punching frequencies were collected. Vo2 values of 43.4 ± 5.9, 41.1 ± 5.1, 24.7 ± 6.1, 30.4 ± 5.8, and 38.3 ± 6.5 ml/kg/min were obtained, which represent 69.7 ± 8.0, 66.1 ± 8.0, 39.8 ± 10.4, 48.8 ± 8.5, and 61.7 ± 10.3%Vo2peak for sparring, pad work, and punching bag at 60, 120, and 180 b/min, respectively. Except for lower Vo2 values for punching the bag at 60 and 120 b/min (p < 0.05), there was no Vo2 difference between exercises. Similar pattern was obtained for %HRmax with respective values of 85.5 ± 5.9, 83.6 ± 6.3, 67.5 ± 3.5, 74.8 ± 5.9, and 83.0 ± 6.0. Finally, sparring %HRmax and [LA] were slightly higher in the GYM (91.7 ± 4.3 and 9.4 ± 2.2 mmol/L) vs. LAB (85.5 ± 5.9 and 6.1 ± 2.3 mmol/L). Thus, in this study simulated LAB sparring and pad work required similar Vo2 (43-41 ml/kg/min, respectively), which corresponds to ~70%Vo2peak. These results underline the importance of a minimum of aerobic fitness for boxers and draw some guidelines for the intensity of training.